Liberalizm Thomasa Paine’a - Błaszczyk, Cezary (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
Thomas Paine was undoubtedly one of the most important figures of his times. The untiring liberal and democrat may be considered as the restless spirit of the Enlightenment, arguing for a revolution and freedom both in Europe and America. His main works are „The Rights of Man”, „First Principles of Government”, „The Agrarian Justice” and the most famous and influential — „Common Sense”. Even though he did not form a comprehensive political doctrine he appealed both to the British and French liberal traditions, he is to be considered as a great liberal ideologist. Paine believed in sovereign and independent men, who under the principle of self-government can establish the best government possible. The state was the necessity, since mankind was prone to sin; however, it was to be constructed according to the civil contract as the least burdensome and in compliance with the rights of men both natural and civil, as a true republic. Moreover, it was only rational, argued Paine, to abandon unequal division of estates and trade protectionism, to allow for universal welfare and peace.
Keywords: Paine, Thomas (1737-1809); liberalizm klasyczny; prawa człowieka; "Zdrowy rozsądek"; umowa społeczna; konstytucjonalizm; własność; prawo do ziemi